Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find the inverse of the function [tex]\( y = \cos^{-1}(x - \pi) \)[/tex], we need to follow a systematic approach:
1. Understand the original function:
[tex]\[ y = \cos^{-1}(x - \pi) \][/tex]
This function represents an inverse cosine function.
2. Switch the variables to find the inverse function:
[tex]\[ x = \cos^{-1}(y - \pi) \][/tex]
3. Solve for [tex]\( y \)[/tex]:
To isolate [tex]\( y \)[/tex], we can follow these steps:
- Apply the cosine function on both sides:
[tex]\[ \cos(x) = y - \pi \][/tex]
- Rearrange to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \pi + \cos(x) \][/tex]
4. Identify the correct option:
We need to compare the final expression [tex]\( y = \pi + \cos(x) \)[/tex] with the provided choices:
- a. [tex]\( y = \pi - \cos(x) \)[/tex]
- b. [tex]\( y = \cos(x - \pi) \)[/tex]
- c. [tex]\( y = \pi + \cos(x) \)[/tex]
- d. [tex]\( y = \cos(x + \pi) \)[/tex]
The correct match is:
[tex]\[ y = \pi + \cos(x) \][/tex]
Therefore, the best answer from the choices provided is:
C
1. Understand the original function:
[tex]\[ y = \cos^{-1}(x - \pi) \][/tex]
This function represents an inverse cosine function.
2. Switch the variables to find the inverse function:
[tex]\[ x = \cos^{-1}(y - \pi) \][/tex]
3. Solve for [tex]\( y \)[/tex]:
To isolate [tex]\( y \)[/tex], we can follow these steps:
- Apply the cosine function on both sides:
[tex]\[ \cos(x) = y - \pi \][/tex]
- Rearrange to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \pi + \cos(x) \][/tex]
4. Identify the correct option:
We need to compare the final expression [tex]\( y = \pi + \cos(x) \)[/tex] with the provided choices:
- a. [tex]\( y = \pi - \cos(x) \)[/tex]
- b. [tex]\( y = \cos(x - \pi) \)[/tex]
- c. [tex]\( y = \pi + \cos(x) \)[/tex]
- d. [tex]\( y = \cos(x + \pi) \)[/tex]
The correct match is:
[tex]\[ y = \pi + \cos(x) \][/tex]
Therefore, the best answer from the choices provided is:
C
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.